2014
DOI: 10.1371/journal.ppat.1004417
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function of Human Pumilio Proteins in Cytoplasmic Sensing of Viral Infection

Abstract: RIG-I-like receptor (RLR) plays a pivotal role in the detection of invading pathogens to initiate type I interferon (IFN) gene transcription. Since aberrant IFN production is harmful, RLR signaling is strictly regulated. However, the regulatory mechanisms are not fully understood. By expression cloning, we identified Pumilio proteins, PUM1 and PUM2, as candidate positive regulators of RIG-I signaling. Overexpression of Pumilio proteins and their knockdown augmented and diminished IFN-β promoter activity induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 49 publications
2
46
1
Order By: Relevance
“…Additionally, immunoprecipition of endogenous PUM proteins resulted in highly significant enrichment of endogenous NORAD (Figure S5C). Consistent with these data, both NORAD (Figure S4D, E) as well as PUM1/PUM2 (Morris et al, 2008; Narita et al, 2014; Ponten et al, 2008) are predominantly localized to the cytoplasm.…”
Section: Resultssupporting
confidence: 84%
“…Additionally, immunoprecipition of endogenous PUM proteins resulted in highly significant enrichment of endogenous NORAD (Figure S5C). Consistent with these data, both NORAD (Figure S4D, E) as well as PUM1/PUM2 (Morris et al, 2008; Narita et al, 2014; Ponten et al, 2008) are predominantly localized to the cytoplasm.…”
Section: Resultssupporting
confidence: 84%
“…Alternatively, some have been shown to participate in antiviral responses early during HSV-1 infection as either positive regulation (e.g. PUM2) (37) or negative regulation (XIAP, SP1) (38). Other proteins that follow the same trend as known viral degradation targets over the time course may represent potential novel candidates for degradation by HSV-1.…”
Section: Fig 1 Proteome Characterization During Hsv-1 Infection By mentioning
confidence: 99%
“…Conversely, Ser/Thr phosphorylation (induced by protein kinase C and casein kinase II), Lys48-linked polyubiquitination, and removal of K63-linked polyubiquitin by several deubiquitinating enzymes (CYLD, USP3 and USP21) inhibit RIG-I activation (reviewed in detail in [2]). Furthermore, it was recently reported that the RNA-binding activity of LGP2 is regulated by Pumilio proteins (PUM1/2) [20]. …”
Section: Cytosolic Sensing Of Vrnamentioning
confidence: 99%